2022
DOI: 10.1136/tobaccocontrol-2021-056879
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco tax evasion in Western Balkan countries: tax evasion prevalence and evasion determinants

Abstract: Background and objectiveTobacco tax evasion undermines the goal of tobacco taxes as a tobacco control measure to make tobacco products less affordable, increases the health risks for those who smoke and decreases the government revenue. This paper analyses the tobacco tax evasion in six Western Balkan (WB) countries: Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia. The aim of this research is to estimate the size of the illicit market and identify the main determinants of tax ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Table 1 presents prices of legal and illegal cigarettes from studies, identified by Goodchild et al , from 2014 to 2020, as well as the most recent studies that we identified 3 32 49. The table shows that, even when the prices are adjusted for purchasing power parity, the variation in illicit cigarette prices is large across the various countries, and the illicit cigarette prices generally follow the prices of legal cigarettes (correlation coefficient: 0.87) 51.…”
Section: Tobacco Prices and Illicit Tradementioning
confidence: 93%
See 1 more Smart Citation
“…Table 1 presents prices of legal and illegal cigarettes from studies, identified by Goodchild et al , from 2014 to 2020, as well as the most recent studies that we identified 3 32 49. The table shows that, even when the prices are adjusted for purchasing power parity, the variation in illicit cigarette prices is large across the various countries, and the illicit cigarette prices generally follow the prices of legal cigarettes (correlation coefficient: 0.87) 51.…”
Section: Tobacco Prices and Illicit Tradementioning
confidence: 93%
“…In the last decade, comprehensive studies of the scope and nature of the illicit cigarette trade have increased. Since 2010, studies independent of the TI have been conducted in at least 40 countries 3 32. Several methods, with their own advantages and limitations,33 have been used to analyse the entirety of the illicit trade problem, from a perspective independent of the TI.…”
Section: New Methods To Measure Illicit Tradementioning
confidence: 99%
“…The papers included in this supplement span the regions of Asia, Latin America, and Southeastern Europe. The research focuses on consumer responses to cigarette price increases (Divino et al, 14 Nguyen et al, 15 Vladisavljevic et al 16 ) as well as their distributional impacts (Cruces et al, 17 Gligorić et al, 18 Divino et al, 19 Cizmovic et al, 20 Nguyen et al 15 ). Two papers analyse tax leakages along the tobacco supply chain: Vladisavljevic et al 16 use data from a primary survey in the Southeastern European region to analyse determinants of tobacco tax evasion and Drope et al examine the regional implications of the tobacco value chain in Paraguay.…”
Section: Editorialmentioning
confidence: 99%
“…The Balkan route is a historical contraband corridor, and the illicit tobacco trade has flourished in the period of transition and conflicts at the end of the 20 th century [8]. A survey on the determinants of illegal tobacco consumption in the Western Balkans region concludes that the consumers of hand-made cigarettes are more willing to smoke illegal tobacco than those used to buy legally manufactured and sold cigarettes [9]. On the other hand, the analysis of consumer attitudes in the same region revealed good public awareness about the negative aspects of the grey tobacco market.…”
Section: Introductionmentioning
confidence: 99%
“…The multidimensional negative effects and the factors influencing the unregulated trade in tobacco, as one of the greatest contemporary global challenges, are the subject of serious research interest [4,[8][9][10][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%